THE LEGAL CONSTRUCTION OF SEXUAL INTERCOURSE AND THE POTENTIAL FOR NUSYUZ: REINTERPRETATION FROM THE PERSPECTIVE OF MAQASID AL-SHARI'AH AND GENDER JUSTICE - Ridwan; Akbarizan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the legal construction of jimak and the potential of nusyus (husband's negligence in fulfilling wife's rights) from the perspective of maqasid al-syari’ah and gender justice. Islamic law emphasizes the husband’s obligation to fulfill sexual, emotional, and financial rights of the wife, but its practice is often influenced by cultural norms, limited legal interpretations, and moral awareness. This study employs a library research method to analyze fiqh literature, legal documents, and case studies. The findings indicate that maqasid-based reinterpretation of jimak law can balance husband and wife rights, reduce nusyus potential, and promote gender justice in the household.